2015
DOI: 10.1155/2015/121826
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Autophagy Induced by Natural Compounds in Prostate Cancer

Abstract: Autophagy is a homeostatic mechanism through which intracellular organelles and proteins are degraded and recycled in response to increased metabolic demand or stress. Autophagy dysfunction is often associated with many diseases, including cancer. Because of its role in tumorigenesis, autophagy can represent a new therapeutic target for cancer treatment. Prostate cancer (PCa) is one of the most common cancers in aged men. The evidence on alterations of autophagy related genes and/or protein levels in PCa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 157 publications
(167 reference statements)
2
39
0
Order By: Relevance
“…Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22). The present study revealed that Res increased autophagosome formation, decreased cell viability and induced apoptotic death in drug-resistant K562/ADM cells.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22). The present study revealed that Res increased autophagosome formation, decreased cell viability and induced apoptotic death in drug-resistant K562/ADM cells.…”
Section: Discussionsupporting
confidence: 70%
“…Res has been shown to induce cell death through various mechanisms in different cancer cell lines (2,11,12,19). Various antitumor effects of Res have been described previously, including the inhibition of DNA polymerase, protein kinase C, cyclooxygenase-2 or interleukin-6 activities, and the suppression of transcription factors such as nuclear factor-κB (4,11,12,21,22).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Normally autophagy is constitutively active at low levels to guarantee cellular homeostasis, but it can be strongly induced in stressful conditions when this process seems to act primarily as a cellular protective response [135]. The effects of EGCG on autophagy seem to be dependent on concentration used, cell type and stress conditions.…”
Section: Autophagymentioning
confidence: 99%